Video classes as advance organizers in health education during the pandemic: experience report (Research, Society and Development, 2020)
Introduction: in the context of the changes caused by the COVID-19 pandemic, tele-education has proved to be a timely and effective alternative to access knowledge. In this sense, the importance of reporting the experiences obtained with video lessons based on the concept of advance organizers is emphasized. Thus, the objective of this experience report is to portray the authors' experience in the theme in question. Experience Report: these are remote activities developed in a public university, for 48 students of the 3rd grade of the medical course. According to the pedagogical precepts of the advance organizers, 19 video classes were given, dealing with mental health issues in general and 16 video classes with clinical cases for the discussion of diagnosis, differential diagnosis and treatment. As an effect, opportunities were generated to begin the deepening of the topics of interest, implying discussions of cases and occurrences of videoconferences to solve the doubts of the students. Discussion: the use of Information and Telecommunications Technologies and active teaching methodology favors an educational alternative during the COVID-19 pandemic. Conclusion:  the experience report demonstrates the use of video files on the digital platform Youtube as advance organizers of a dynamic teaching process. It is concluded that the adoption of these strategies in distance education during the current crisis experienced in the field of medical education is feasible and efficient.